Recent Publications (Quarterly Journal of Economics, 1966)
Recent Publications The Quarterly Journal of Economics, Volume 80, Issue 4, November 1966, Pages 660–663, https://doi.org/10.1093/qje/80.4.660 Published: 01 November 1966